SLIP EFFECTS ON MHD STAGNATION-POINT FLOW OF CARREAU FLUID PAST A PERMEABLE SHRINKING SHEET - Arifin, Norihan; Yusof, Siti; Ismail, Nurul (MATTER: International Journal of Science and Technology, 2017)
Carreau fluidis a type generalised fluid where viscosity depends upon the shear rate of the fluid and thenuses it to obtain a formulation for the boundary layer equations of the Carreau fluidThe objective of the present study is to analyze the development of the slip effect on the MHD stagnation-point flow of Carreau fluid past a shrinking sheet. The mathematical modeling of Carreau fluid has been developed for boundary layer problem and the governing partial differential equations are transformed into ordinary differential equation using self-similarity transformation. The effect of velocity slip is taken into account and controlled by non-dimensional parameter. The dual solutions are obtained when the sheet is shrunk. The study shows that the skin friction decreases with an increase in velocity slip.